On the Equivalence of Module Categories over a Group-Theoretical Fusion Category - Natale, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We give a necessary and sufficient condition in terms of group cohomology for two indecomposable module categories over a group-theoretical fusion category C to be equivalent. This concludes the classification of such module categories.